Abundance, color pattern variation, life cycle, and reproduction of the triploid parthenogenetic lizard Aspidoscelis uniparens (Squamata: Teiidae) in Chihuahua, Mexico - Walker, James M.; Lemos-Espinal, Julio A.; Cordes, James E.; Smith, Hobart M. (Phyllomedusa: Journal of Herpetology, 2018)
Abundance, color pattern variation, life cycle, and reproduction of the triploid parthenogenetic lizard Aspidoscelis uniparens (Squamata: Teiidae) in Chihuahua, Mexico. We have observed the triploid parthenogenetic lizard Aspidoscelis uniparens in syntopy with many congeners, as well as allopatric to them, within a distribution area in parts of Arizona, New Mexico, and Texas (USA), and Chihuahua and Sonora (Mexico). In July 2000, we discovered arrays (= groups) of A. uniparens with distinctive dorsal color patterns, allopatric to congeners, at a cluster of three sites in northwestern Chihuahua. These arrays were distinguishable based on strikingly different dorsal color patterns. Thus, we designated specimens from two mapped sites in the Municipality of Casas Grandes and from one nearby mapped site in the Municipality of Nuevo Casas Grandes as vividly striped lizards (VSL). Specimens from other mapped sites were designated normally striped lizards (NSL). We observed that the three VSL sites along the base of foothills of the eastern slope of the Sierra Madre Occidental were ecologically different from NSL sites such as El Sueco and Pradera de Janos in central and northwestern Chihuahua, respectively. All VSL specimens possessed wider and more vividly hued primary stripes, whereas the stripes were of normal width and low-contrast color hues in samples NSL-1 and NSL-2. We used samples NSL-1, NSL-2, and VSL for statistical comparisons of means ± 1 SE for the following characters: snout‒vent length (the three arrays had similar maximum SVL measurements and mean differences attributable to the year-class structure of samples); number of granular scales between the paravertebral stripes at midbody (revealing signifcant differences between some samples); percent of granular scales around midbody situated between the paravertebral stripes at midbody (revealing signifcant differences between all samples); percent of the vertebral feld with a vertebral stripe (revealing signifcant differences between some samples); and clutch size (revealing signifcant differences between some samples). We concluded that qualitative characters diagnostic of the VSL sample of A. uniparens were not accompanied by unique quantitative characters.